(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The research mainly aims to identify the extent to which physics books in high school in Iraq meet the content standards of the International Physics Olympic Competition. In order to achieve the main aim of the research, the researcher limited the subjects of the competition to the descriptive analytical method, which based on the content analysis that has been used is considered to be a suitable way for the analysis of curricula and to collect the quantitative data. The analysis tool included subjects and a graduated scale consisting of three categories: the extent of the handling, the form of handling, and the level of handling. The research community consisted of all physics books in high schools in Iraq, which are 5 books spread over three grades which are established to be taught for the academic year (2019 2018) reliability and validity evidence were gathered, and the frequencies and percentages were used as statistical means to determine the extent to which those subjects are approached . The research found a set of results, which are that the subjects of oscillation and waves, electromagnetic fields, and mechanics were more addressed than subjects of thermodynamics quantum physics and relativity. The form of handling was fairly acceptable as the percentage was (%) explicit and physics the level of subj(%) 50,was (%50) which is very low percentage. It is also recommended that it is important to pay attention to the quality and depth of information to suit the level of mental learner the study also suggested conducting similar study to evaluate mathematics. computer and chemistry curricula in light of the Olympic Competition held for each subjects.